An object-oriented data model built for blind navigation in outdoor space. (June 2015) - Chen, Min; Lin, Hui; Liu, Deer; Zhang, Hongping; Yue, Songshan
Abstract: Increasing research has been conducted to improve navigation services for the blind when they are moving through an outdoor space. This article aims to propose a formal modeling approach helps facilitate decision making about navigation pathways. The proposed data model is based on an objective orientation idea. City features, such as street features, buildings and environmental areas, are organized as a series of function objects that meet the various needs of the blind. They are linked by paths with obstacles and irregular surface objects. A complex function object is composed of several inner function objects and paths; thus, it can reflect the spatial layout at various levels. Detailed semantic content can be added into the objects as an extension that enhances the representation and facilitates spatial learning. The geometric shapes of the proposed objects and their topological information are also recorded for local navigation and comprehensive path planning. To examine the usability of the data model, a prototype system was developed using the Chinese university of Hong Kong as a study area, and test cases are illustrated for a typical designed scenario. Highlights: We proposed an object-oriented data model for blind navigation in outdoor space. City features are organized as a series of function objects. Function objects are linked by paths with obstacles and irregular surface objects. Detailed semantic content can be added into the data model. The geometric and topological information are recorded in the data model.